REVIEW ON HERPES SIMPLEX VIRUS: CAUSES, AVAILABLE DRUGS AND FUTURE PROSPECTS - SMRITI SINGH; PRANJIL KULSHRESTHA; MAYANK AGARWAL (International Journal of Pharma and Bio Sciences, 2015)
Herpes simplex virus (HSV-1 and HSV-2) is one of the disease which is found all over the world. It causes cold sore or watery blisters on the skin and the mucous membrane of mouth or genitals, and they are contagious and ubiquitous. It can spread with the contact of the saliva of the infected person. After the primary infection the virus undergoes latent phase in the cell bodies of neurons which may reactivate if favorable condition is provided. At present many antiviral drugs were suggested for the treatment of disease and these have been suggested by many computational and wet lab studies. Drugs like Acyclovir and other are available in the market for the treatment of HSV but problems like drug resistance prevent them to provide an efficient and prolong treatment of the disease. In this study, an analysis of natural and chemical compounds were done which are reported to inhibit various targets (Proteins) to suppress Herpes Simplex Virus disease.